PENGARUH PERAN AUDITOR INTERNAL DAN PELAKSANAAN FUNGSI MANAJEMEN KEUANGAN DALAM PENGELOLAAN PENERIMAAN NEGARA BUKAN PAJAK TERHADAP KINERJA KEUANGAN UNIVERSITAS RIAU - Mariadi, Mariadi; Hasan, Amir (Jurnal Tepak Manajemen Bisnis, 2018)
The Influence Of The Role Of Internal Auditors And TheImplementation Of Financial Management Functions In The Management Of Non-Tax Revenue To The Financial Performance Of The University Of Riau. Financialperformance is the level of achievement of results of an activity within a government /non-government agency in relation to the use of funds in accordance with quantity andquality measured using the principles of efficiency and effectiveness. Universities as oneunit of government work units that provide services to the community havecharacteristics and properties different from the work unit of government in general Atthe University of Riau the implementation of financial management functions have longbeen implemented in the implementation has not been running as it should. Accordingto the evaluation result of Riau University governance system in the book of StrategicPlan 2014, Financial management has not fulfilled the principles of transparency andaccountability caused by still constrained by the current financial management system.The formulation of the problem in this research is whether there is influencesimultaneously the role of internal auditor and the function of financial management inthe management of non-tax revenue to the performance of Finance University of Riau.This research uses quantitative descriptive method. The nature of this research isdescriptive explanatory research with 63 respondents.The results showed that there is a significant influence between the role of internalauditors on the financial performance of the University of Riau and also there is asignificant influence between the variable implementation of financial managementfunctions to variable financial performance of the University of Riau. Simultaneouslythe role of internal auditors and the implementation of financial management functionsaffect the financial performance of the University of Riau in managing Non-Tax StateRevenue Management, with a very significant level of influence. Where from thedetermination koefisien R2 known that the discipline and supervision variables have aninfluence of 77.4% and the remaining 22.6% influenced by variables not examined inthis study.